Effectiveness Of Low-Intensity Exercise and Cognitive Behavioral Therapy In Female Patients with Fibromyalgia - K.Senthil, K.Senthil; Pragassame, S.Arul; Raj, G.Mohan; Paruthirajan, S. (Journal of Neonatal Surgery, 2025)
Background: Fibromyalgia (FM) is a chronic neuroendocrine syndrome characterized by physical symptoms such as widespread pain, fatigue, and other psychological symptoms. This study aimed to reveal the effectiveness of low-intensity exercise and cognitive behavioral therapy for insomnia (CBT-i) on pain catastrophizing, endurance, quality of life (QoL), and quality of sleep among female patients with FM. Methodology: A randomized controlled trial was conducted with 30 female patients with FM who were chosen based on the selection criteria. By using simple random sampling, those patients were randomly allocated to Group A and Group B. Group A (n=15) received a low-intensity exercise program combined with CBT-i, and Group B (n=15) received CBT including counseling, pain coping strategies such as mental imagery and relaxation techniques for a period of six weeks. Results: Outcome variables such as pain catastrophizing, endurance, QoL, and quality of sleep were assessed before and after intervention. After treatment duration, all outcome variables significantly improved in Group A and Group B. Conclusion: Group A treated with a low-intensity exercise program with CBT-i was found to be more effective in reducing pain catastrophizing and improving endurance, QoL, and quality of sleep than Group B treated with CBT only. A low-intensity exercise program with CBT-i would be beneficial in managing FM cases. Future studies can be conducted with a larger sample size of genders, long treatment duration, and follow-up measurements.